The Influence of Mind Map-Based Expository Learning Strategy Using Canva on Mathematics Learning Outcomes of Grade VIII Students of Junior High School 1 Pandan, Indonesia - Hutagalung, Herdiansyah (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2025)
This research is motivated by the low learning outcomes of class VIII mathematics students. One of the causes of low student learning outcomes is the use of inappropriate learning strategies that are less interesting for students in the learning process. The purpose of this study was to determine and analyze the influence of mind map-based expository learning strategies using Canva on the mathematics learning outcomes of class VIII students at Pandan 1 Middle School. One strategy that is considered capable and in line with technological developments is an expository learning strategy based on mind maps using Canva. The research population, namely all class VIII students and the sample consisted of two classes, namely the experimental class and the control class. The research instrument used a test. While data processing and data analysis were carried out using the t-test. Based on data analysis, the post-test questions given to students to measure students' cognitive abilities obtained an average value of 76.11 for the experimental class and 64.69 for the control class. The results of the hypothesis test obtained tcount>ttable, namely 2.163>1.99897 with a significance level of 5%, so Ha is accepted and H0 is rejected, which means that there is a significant influence on the expository learning strategy based on mind maps using Canva on the mathematics learning outcomes of class VIII students of SMP N 1 Pandan.